Dynamic colloidal nanoparticle assembly triggered by aptamer–receptor interactions on live cell membranes. Issue 31 (28th June 2019) - Yang, Linlin; Meng, Lingyan; Song, Jiaying; Xiao, Yue; Wang, Ruowen; Kang, Huaizhi; Han, Da
Abstract : We engineered an aptamer and DNA displacement reaction-based dynamic system that can transform its shape in response to epithelial cell adhesion molecule (EpCAM) on live cell membranes. Abstract : Cells use dynamic systems such as enzyme cascades and signaling networks to control cellular functions. Synthetic dynamic systems that can be target-responsive have great potential to be applied for biomedical applications but the operation of such dynamic systems in complex cellular environments remains challenging. Here, we engineered an aptamer and DNA displacement reaction-based dynamic system that can transform its nanostructure in response to the epithelial cell adhesion molecule (EpCAM) on live cell membranes. The dynamic system consisted of a core nanoparticle and small satellite nanoparticles. With the modifications of different DNA hairpin strands and swing arm strands partially hybridized with an aptamer that specifically recognizes the EpCAM, the two separated particles can dynamically assemble into a core–satellite assembly by aptamer–receptor interactions on the cell membrane surface. The structural change of the system from separated particles to a core–satellite assembly generated plasmonic coupled hot spots for surface-enhanced Raman scattering (SERS) for sensitively capturing the dynamic structural change of the nanoassembly in the cellular environment. These concepts provide strategies for engineering dynamic nanotechnology systems for biological and biomedical applications in complex biological environments.